Dinamika Agroklimat, Nilai Tukar Petani, dan Kontribusi PDRB Subsektor Jagung di Nusa Tenggara - Siti Danisha Ameera (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
Corn production in the provinces of East Nusa Tenggara (NTT) and West Nusa Tenggara (NTB) exhibits dynamics influenced by agro-climatic factors, the utilization of production facilities, and the welfare condition of the farmers. This study aims to analyze the impact of rainfall, solar radiation, and production inputs on corn productivity; to explain the relationship between production changes and the Farmer’s Exchange Rate (NTP) as a welfare indicator; and to evaluate the contribution of the corn subsector to the agricultural Gross Regional Domestic Product (GRDP). The research method uses a descriptive-quantitative approach based on BPS data and official local government documents. The results indicate that NTB has more stable productivity due to relatively even rainfall and better support for production facilities, whereas NTT faces higher production fluctuations due to greater climate variability. Furthermore, the NTP in NTB tends to be better than in NTT, aligning with the stability of its productivity. Corn contributes significantly to the agricultural GRDP in both provinces, particularly in central production areas such as Dompu and Bima. Policy implications include the necessity for strengthening post-harvest infrastructure, more equitable input distribution, and climate adaptation strategies in drought-prone areas. The findings provide an empirical basis for sustainable productivity improvement and farmer welfare policies.